Safety and efficacy of a feed additive consisting of Bacillus velezensis ATCC PTA‐6737 (Bacillus velezensis PB6) for turkeys for fattening, turkeys reared for breeding, laying hens, minor poultry species for laying, piglets (weaned), weaned minor porcine species and sows (Kemin Europe N.V.) - EFSA Panel on Additives and Products or Substances used in Animal Feed (FEEDAP); Vasileios Bampidis; Giovanna Azimonti; Maria de Lourdes Bastos; Henrik Christensen; Birgit Dusemund; Mojca Fašmon Durjava; Maryline Kouba; Marta López‐Alonso; Secundino López Puente; Francesca Marcon; Baltasar Mayo; et al. (EFSA Journal, 2022)
Abstract Following a request from the European Commission, EFSA was asked to deliver a scientific opinion on the safety and efficacy of Bacillus subtilis ATCC PTA‐6737 (Bacillus subtilis PB6) when used as a feed additive for turkeys for fattening, turkeys reared for breeding, laying hens, minor poultry species for laying, piglets (weaned), weaned minor porcine species and sows. With this application, the company requested the modification of the current authorisations as regards the strain taxonomy from B. subtilis ATCC PTA‐6737 to Bacillus velezensis ATCC PTA‐6737. The FEEDAP Panel concluded that the active agent of B. subtilis PB6 should be taxonomically designated as B. velezensis ATCC PTA‐6737. The Panel also concluded that Bacillus velezensis PB6 is presumed safe for the target species, consumers and the environment and is not a dermal/eye irritant or a skin sensitiser but should be considered a respiratory sensitiser. The Panel reiterated the previous conclusions reached on the efficacy of the additive when used with the target species.